ANALYSIS OF FACTORS IMPULSIVE BUYING (Case Study in Suzuya Lhokseumawe Mall) - Adnan; Desi Ariani Rahayu; Siti Maimunah; T. Edyansyah (RADJA PUBLIKA, 2024)
This research aims to determine and analyze the magnitude of the influence of implosive buying factors at Suzuya Mall, Lhokseumawe city and to find out which factors have the most dominant influence on impulsive buying at Suzuya Mall, Lhokseumawe city. The factors that influence impulsive buying in this research are Fashion Involvement, shopping lifestyle, and Store Atmosphere. Where data from these variables is taken using the incidental sampling technique, which is part of non-probability sampling. Where all these variables will be measured using an ordinal scale. The data used in this research is primary data obtained by distributing questionnaires to 100 respondents who made purchases at Suzuya Mall, Lhokseumawe city. The data analysis technique used is multiple linear regression with the help of SPSS software. The research results show that Fashion Involvement, shopping lifestyle, and Store Atmosphere have a positive and significant effect on impulsive buying at Suzuya Mall, Lhokseumawe city. Meanwhile, the results of the coefficient of determination test showed that implosive buying at Suzuya Mall, Lhokseumawe city was influenced by Fashion Involvement, shopping lifestyle and Store Atmosphere by 64 percent.